Intensive Care Unit Management of Right Heart Failure and Lung Transplantation for Pulmonary Hypertension - Beale, Anna; Safavi, Sahideh; Granton, John (Current Respiratory Medicine Reviews, 2024)
Pulmonary hypertension is associated with worse outcomes across systemic and cardiopulmonary conditions. Right ventricular (RV) dysfunction often leads to poor outcomes due to a progressive increase in RV afterload. Recognition and management of RV dysfunction are important to circumvent hospitalization and improve patient outcomes. Early recognition of patients at risk for RV failure is important to ensure that medical therapy is optimized and, where appropriate, referral for lung transplant assessment is undertaken. Patients initiated on parenteral prostanoids and those with persistent intermediate to high risk for poor outcomes should be referred. For patients with RV failure, identifying reversible causes should be a priority in conjunction with efforts to optimize RV preload and strategies to reduce RV afterload. Admission to a monitored environment where vasoactive medications can treat RV failure and its sequelae, such as renal dysfunction, is essential in patients with severe RV failure. Exit strategies need to be identified early on, with consideration and implementation of extracorporeal support for those in whom recovery or transplantation are viable options. Enlisting the skills and support of a palliative care team may improve the quality of life for patients with limited options and those with ongoing symptoms from heart failure in the face of medical treatments.
Keywords: Pulmonary hypertension